Effects of Icariin on Modulating Gut Microbiota and Regulating Metabolite Alterations to Prevent Bone Loss in Ovariectomized Rat Model - Wang, Shanshan; Wang, Shengjie; Wang, Xiaoning; Xu, Yunteng; Zhang, Xin; Han, Yidan; Yan, Hui; Liu, Linglong; Wang, Lili; Ye, Hongzhi; Li, Xihai (Frontiers in Endocrinology, 2022)
Postmenopausal osteoporosis (PMOP) is an estrogen deficiency-induced bone loss, which has been shown an association with an altered gut microbiota (GM). Gut microbiota-bone axis has been recognized as a crucial mediator for bone homeostasis. Icariin (ICA) is an effective agent to delay bone loss by regulating the bone homeostasis. Thus, we hypothesize that ICA can prevent bone loss by modulating GM and regulating metabolite alterations. The effects of ICA on bone metabolism improvement in ovariectomized (OVX) rats and their relationships with the GM and fecal metabolites were investigated. Micro-computed tomography (micro-CT) and hematoxylin-eosin (HE) staining showed a typical bone boss in OVX group, while ICA or estradiol (E2) administration exhibited positive effects on bone micro-architecture improvement. The GM such as Actinobacteria, Gammaproteobacteria, Erysipelotrichi, Erysipelotrichales, Enterobacteriales, Actinomycetales, Ruminococcus and Oscillospira significantly correlated to serum bone Gla-protein (BGP), receptor activator of nuclear factor-κB (RANK), receptor activator of nuclear factor-κB ligand (RANKL), osteoprotegerin (OPG) and tartrate resistant acid phosphatase (TRACP). Further t-test revealed a substantial variation of the GM and fecal metabolites in different treatments. Among them, Lachnoclostridium, Butyricimonas, Rikenella, Paraprevolla, Adlercreutzia, Enterorhabdus, Anaerovorax, Allobaculum, Elusimicrobium, Lactococcus, Globicatella and Lactobacillus were probably the key microbial communities driving the change of bile acid, amino acid and fatty acid, thereby leading to an improvement of PMOP. The significant up-regulation of L-Saccharopine, 1-Aminocyclohexadieneacid and linoleic acid after ICA administration suggested important contributions of amino acid and fatty acid metabolisms in the prevention and treatment of PMOP. Taken together, our study has provided new perspectives to better understand the effects of ICA on PMOP improvement by regulating GM and the associated fecal metabolites. Our findings contribute to develop ICA as a potential therapy for PMOP.